Schools: Trends and perspectives - Katafygiotou, Martha; Serghides, Despina Kyprianou (My University, 2015)
This chapter’s emphasis is on existing school buildings, with an overview of the European and, more specifically, the Mediterranean region. Following the overview of schools in the Mediterranean region, the study focuses on secondary schools in Cyprus. It identifies the prevailing building practices in school construction with specific reference to the schools in Cyprus. The construction and energy consumption details of the secondary school buildings in Cyprus are also presented. Indoor comfort and energy efficiency are analyzed through questionnaires, surveys, interviews, and simulations on specific pilot school buildings. The field studies are conducted to evaluate the indoor thermal conditions during the students’ classes. Further investigation of the energy efficiency of schools is carried out through building simulations. Existing situations, current trends and tendencies of schools provide essential information to facilitate the energy performance assessment of the building stock and to highlight the potential of energy savings and the upgrading of their indoor comfort.
Keywords: School buildings; Mediterranean region; Secondary schools; Cyprus